Identification of field and gardenpea (Pisum sativum) varieties using RAPD and ISSR markers - R.K. KAPILA,; S. NARYAL,; K.C. DHIMAN,; S.K. SINGH,; J.K. SHARMA, (Seed Research, 2026)
Identification of seven varieties of garden and field pea (Pisum sativum L.) currently under seed multiplication chain in Himachal Pradesh was undertaken using 40 random decamer and 9 ISSR primers. A total of 251 amplicons including 111 RAPDs and 70 ISSRs bands were amplified. The ISSR markers exhibited better polymorphism and resolving power as compared to RAPDs. High pair-wise genetic similarity estimates ranging from 0.50 to 0.86 indicated narrow genetic base of the set of varieties. Clustering analysis based on pooled data grouped 7 varieties in 3 main groups. Four gardenpea varieties comprised one main group, whereas a field pea along with one gardenpea variety constituted other group. Field pea variety, Rachna, was most divergent from other varieties and did not group with any other varieties. All the 7 varieties were resolved completely using variety specific and/or other polymorphic markers amplified using single ISSR and RAPD primers, namely UBC 843 and OPJ 14, respectively. Four random decamer and 6 ISSR primers were identified as potential ones that could alone distinguish 5 or more varieties, out of a set of total 7 varieties. Study indicated possible use of variety-specific amplicons in developing diagnostic kits for identification of current set of pea varieties under cultivation in Himachal Pradesh.